2006
DOI: 10.1016/j.ejheart.2005.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II AT1 receptor density on blood platelets predicts early left ventricular remodelling in non‐reperfused acute myocardial infarction in humans

Abstract: Background: Renin -angiotensin-system activity, a principal factor determining ventricular remodelling after myocardial infarction (MI), is dependant on local angiotensin II concentration and angiotensin AT 1 receptor (AT 1 R) density. The latter is regulated by systemic factors acting independently from angiotensin II concentration. Objective: To test the hypothesis that AT 1 R density at the onset of MI determines post-MI ventricular remodelling. Methods: In 48 patients with first acute MI who did not underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In the previous study we showed that high AT 1 R density on blood platelets drawn on average within 13 h from the onset of myocardial infarction was a strong and independent predictor of early remodeling (pre-discharge day 8 echocardiography) [7]. Now we extend these observations by showing that this effect is retained after 6 months.…”
Section: Angiotensin At 1 Receptor Density and Post-mi Remodelingsupporting
confidence: 76%
See 3 more Smart Citations
“…In the previous study we showed that high AT 1 R density on blood platelets drawn on average within 13 h from the onset of myocardial infarction was a strong and independent predictor of early remodeling (pre-discharge day 8 echocardiography) [7]. Now we extend these observations by showing that this effect is retained after 6 months.…”
Section: Angiotensin At 1 Receptor Density and Post-mi Remodelingsupporting
confidence: 76%
“…Since LVESVI and EF are indices of systolic function, while LVEDVI is rather an index of dilation, this would suggest that AT 1 R density is a better predictor of post-MI function than post-MI dilation, although larger studies are needed to support this conclusion. Additionally correlation coefficients at 6 months were significantly poorer than 8 days after the infarction [7]. This indicates that AT 1 R density is a strong predictor of ventricular remodeling after myocardial infarction but strength of this effect decreases over time.…”
Section: Angiotensin At 1 Receptor Density and Post-mi Remodelingmentioning
confidence: 89%
See 2 more Smart Citations
“…Angiotensin II receptor 2 (AT2R) is thought to cause opposite effects of AT1R. In post-myocardial infarction patients, a higher density of AT-1 receptor density, as detected on blood platelets, may confer a greater risk of undergoing ventricular remodeling for up to 6 months after an infarction [17,18].…”
Section: B Renin-angiotensin-aldosterone System Regulationmentioning
confidence: 99%